THE ROLE OF MILITARY TERMS IN GENERAL MILITARY REGULATIONS (American Journal of Pedagogical and Educational Research, 2023)
Military terminology refers to the terms and language of military organizations and personnel as belonging to a discrete category. As distinguishable by their usage in military doctrine, they serve to depoliticise, dehumanise, or otherwise abstract discussion about its operations from an actual description thereof